Hepatoprotective Activity of Terminalia arjuna Leaf Against Paracetamol-Induced Liver Damage in Rats - Biswas, Moulisha; K. Karan, Tarun; Kar, Biswakanth; Bhattacharya, Sanjib; K. Ghosh, Ashoke; Suresh Kumar, R.B.; K. Haldar, Pallab (Asian Journal of Chemistry, 2010)
In present study, the methanolic extract of Terminalia arjuna was evaluated for its protective effect on paracetamol-induced liver damage in Wistar rats. Serum biochemical parameters viz., serum glutamine oxaloacetate transaminase, serum glutamine pyruvate transaminase, serum alkaline phosphatase (SALP), total protein, bilirubin, cholesterol, triglyceroides and liver biochemical parameters such as lipid peroxidation, reduced glutathione (GSH) content and catalase (CAT) activity were estimated. Serum and liver biochemical observations indicated that methanolic extract of Terminalia arjuna exerted remarkable hepatoprotective efficacy against paracetamol-induced hepatic damage in Wistar rats that is may be due to its augmenting endogenous antioxidant mechanisms.